Secondary school students’ awareness and perception toward Manjung Community College: Acase study on local understanding of TVET in fashion and apparel. - Zulkifli, Muhammad Ikhwan Syafiq; Shamsuddin, Shazwani Farhah; Shamsuddin, Shazwani Farhah (Jurnal Penyelidikan Sains Sosial, 2025)
This study explores the level of awareness and perception among local secondary school students towards Manjung Community College, a TVET institution offering the Fashion and Apparel Certificate programme. In recent years, the college have seen a worrying decline in enrolment, prompting concerns about the institution’s visibility and public perception. Using a mixed-methods research design, the study collected data through questionnaires and an open-ended question among students from five selected schools in the Manjung district. The findings revealed that overall awareness of the college stands at 63%, with significant variability across schools. Teachers and school counsellors were identified as the primary sources of information, while social media had minimal influence. Students showed generally positive perceptions towards TVET programmes but remained hesitant about enrolling, preferring traditional academic universities. Factors such as communication gaps, societal stigma towards TVET, and ineffective digital outreach were identified as key challenges faced. The study recommends enhancing teacher and counsellor’s engagement, conducting targeted school campaigns, leveraging peer influence, and strengthening digital marketing strategies through platforms like TikTok and Instagram to improve visibility and enrolment targeting Generation Z. The findings offer valuable insights for Manjung Community College and similar institutions aiming to revitalize student interest in TVET programmes.